2021
DOI: 10.1101/2021.06.17.448820
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 spike P681R mutation, a hallmark of the Delta variant, enhances viral fusogenicity and pathogenicity

Abstract: During the current SARS-CoV-2 pandemic, a variety of mutations have been accumulated in the viral genome, and at least five variants of concerns (VOCs) have been considered as the hazardous SARS-CoV-2 variants to the human society. The newly emerging VOC, the B.1.617.2 lineage (delta variant), closely associates with a huge COVID-19 surge in India in Spring 2021. However, its virological property remains unclear. Here, we show that the B.1.617 variants are highly fusogenic and form prominent syncytia. Bioinfor… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
64
0
8

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(75 citation statements)
references
References 80 publications
3
64
0
8
Order By: Relevance
“…It was observed that the variants carrying spike L452R change are likely to be more transmissible and infective and less susceptible to the neutralizing antibodies from convalescent patients and vaccine recipients (Deng et al, 2021). The variant bearing P681R, such as B.1.617.2, has an increased furin-mediated cleavage at the S1/S2 cleavage site that would lead to enhanced viral fusogenicity and exhibit a higher pathogenicity (Liu et al, 2021b;Peacock et al, 2021;Saito et al, 2021). It was also observed that in the hamster model, B.1.617.1 has a higher pathogenicity than has B.1 (Yadav et al, 2021a).…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that the variants carrying spike L452R change are likely to be more transmissible and infective and less susceptible to the neutralizing antibodies from convalescent patients and vaccine recipients (Deng et al, 2021). The variant bearing P681R, such as B.1.617.2, has an increased furin-mediated cleavage at the S1/S2 cleavage site that would lead to enhanced viral fusogenicity and exhibit a higher pathogenicity (Liu et al, 2021b;Peacock et al, 2021;Saito et al, 2021). It was also observed that in the hamster model, B.1.617.1 has a higher pathogenicity than has B.1 (Yadav et al, 2021a).…”
Section: Introductionmentioning
confidence: 99%
“…L452R mutation in the RBD was reported to increase SARS-CoV-2 infectivity and fusogenicity 21 . P681R, a highly conserved mutation in the B.1.617 lineages, also enhanced SARS-CoV-2 Spike-mediated cell-cell fusion 22 . At the time of preparing this manuscript, the B.…”
Section: Discussionmentioning
confidence: 98%
“…Up to June 2021, several variants of concern for which there is evidence of an increase in transmissibility and reduced effectiveness of treatments or vaccines have been reported. These include B.1.1.7 (alpha variant), B.1.351 (beta variant), P.1 (gamma variant), and B.1.617.2 (delta variant), first identified in the United Kingdom, South Africa, Japan/Brazil, and India, respectively (CDC, 2021;Saito et al, 2021). Mutations of concern include the P681R mutation in the S protein of B.1.617.2, close to the furin cleavage site, which may increase the rate of S1/S2 cleavage and enhance viral fusion (Cherian et al, 2021;Saito et al, 2021).…”
Section: Perspectivesmentioning
confidence: 99%
“…These include B.1.1.7 (alpha variant), B.1.351 (beta variant), P.1 (gamma variant), and B.1.617.2 (delta variant), first identified in the United Kingdom, South Africa, Japan/Brazil, and India, respectively (CDC, 2021;Saito et al, 2021). Mutations of concern include the P681R mutation in the S protein of B.1.617.2, close to the furin cleavage site, which may increase the rate of S1/S2 cleavage and enhance viral fusion (Cherian et al, 2021;Saito et al, 2021). Fortunately, a reverse genetic system for SARS-CoV-2 has been developed to generate mutants of the virus, which could be used to examine effects of the furin cleavage site's deletion on virus replication and facilitate analyses of the replication and pathogenicity of the virus (Xie et al, 2020;Johnson et al, 2021).…”
Section: Perspectivesmentioning
confidence: 99%